Treatment non surgical in a young girl with facial asymmetry, severe crowding and partial cross bite. - Gallardo Moreno, Wenceslao (Revista Universidad de Guayaquil, 2013)
The patient was a 13 years 7 months old, with facial asymmetry, partial unilateral crossbite on the right side, and severe crowding in the maxillary arch. Tells symptoms and signs usually associated with temporomandibular disorder, noise and joint pain, muscle fatigue, mouth closure problems. She was treated with orthodontics through the extraction of four first premolars and the alignment of the upper and lower dental arches, the surgical approach in relation to the asymmetry was dismissed, didnot care or the girl or her mother. The total active treatment time was 26 months. Records pre and post-treatment are shown. His facial appearance and occlusion significantly improved by orthodontic treatment. Records after treatment after 4 years showed excellent results with good occlusion and long-term stability. Shows the effect of a treatment strategy without side effects.
Keywords: facial asymmetry; crossbite; crowding; temporomandibular joint dysfunction; malocclusion; dysfunctions of the language